Triggers of KPTS Policy Conflict and Poverty Alleviation with the Mopohulinta Approach - Harson Towalu (Westscience Press, 2024)
The purpose of this study is to describe the Triggers of KPTS Policy Conflict in Poverty Alleviation in Pohuwato Regency, Gorontalo Province. This study uses descriptive and analytical methods. The results of the study indicate that the triggers of KPTS Policy Conflict in poverty alleviation in Pohuwato Regency are central government policies and global situations that are irrelevant and do not contribute to the implementation of KPTS. This study also produces recommendations in the form of the need for innovation in local wisdom value policies with the Mopohulita model.